1995
DOI: 10.1128/jvi.69.11.6972-6979.1995
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the capacity of reovirus strains to induce apoptosis are determined by the viral attachment protein sigma 1

Abstract: Reoviruses are important models for studies of viral pathogenesis; however, the mechanisms by which these viruses produce cytopathic effects in infected cells have not been defined. In this report, we show that murine L929 (L) cells infected with prototype reovirus strains type 1 Lang (T1L) and type 3 Dearing (T3D) undergo apoptosis and that T3D induces apoptosis to a substantially greater extent than T1L. Using T1L ؋ T3D reassortant viruses, we found that differences in the capacity of T1L and T3D to induce a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
143
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(153 citation statements)
references
References 74 publications
7
143
3
Order By: Relevance
“…In cultured cells, MRV-induced apoptosis is not dependent on de novo synthesis of viral RNA and protein (Connolly and Dermody, 2002;Danthi et al, 2006), indicating that components of the incoming viral capsid are sufficient for initiation of prodeath signaling. Consistent with these findings, differences in the capacity of prototype reovirus strains to induce apoptosis segregate genetically with the S1 and M2 gene segments (Tyler et al, 1995(Tyler et al, , 1996Connolly et al, 2001), which encode the viral attachment protein σ1 and the viral membrane penetration protein μ1, respectively (McCrae and Joklik, 1978;Mustoe et al, 1978). Although initial studies suggested that attachment of MRV σ1 with JAM-A or sialic acid on the host cells is important for apoptosis Connolly et al, 2001), antibody-dependent uptake of MRV virions into host cells in a JAM-A-and sialic acid-independent manner also leads to apoptotic cell death, indicating that signaling pathways triggered by σ1-receptor interactions are dispensable for MRV-induced apoptosis (Danthi et al, 2006).…”
Section: Apoptosis Induction By Delivery Of Viral Components Into Thesupporting
confidence: 57%
“…In cultured cells, MRV-induced apoptosis is not dependent on de novo synthesis of viral RNA and protein (Connolly and Dermody, 2002;Danthi et al, 2006), indicating that components of the incoming viral capsid are sufficient for initiation of prodeath signaling. Consistent with these findings, differences in the capacity of prototype reovirus strains to induce apoptosis segregate genetically with the S1 and M2 gene segments (Tyler et al, 1995(Tyler et al, , 1996Connolly et al, 2001), which encode the viral attachment protein σ1 and the viral membrane penetration protein μ1, respectively (McCrae and Joklik, 1978;Mustoe et al, 1978). Although initial studies suggested that attachment of MRV σ1 with JAM-A or sialic acid on the host cells is important for apoptosis Connolly et al, 2001), antibody-dependent uptake of MRV virions into host cells in a JAM-A-and sialic acid-independent manner also leads to apoptotic cell death, indicating that signaling pathways triggered by σ1-receptor interactions are dispensable for MRV-induced apoptosis (Danthi et al, 2006).…”
Section: Apoptosis Induction By Delivery Of Viral Components Into Thesupporting
confidence: 57%
“…Inhibitors were added immediately following adsorption. The percentage of dead cells after 48 h of incubation was determined by using acridine orange-ethidium bromide (AOEB) staining as described previously (82). For identifying host regulators of cell death, cells were transfected with siRNA as described above and incubated for 48 h prior to infection with T3D.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…DNAcontaining viruses that induce apoptosis include adenoviruses (Rao et al, 1992;Chiou et al, 1994;Antoni et al, 1995), Epstein±Barr virus (Gregory et al, 1994), and poxviruses (Ray et al, 1992;Hu et al, 1994). Several RNAcontaining viruses have also been reported to induce apoptosis: these include polioviruses (Tolskaya et al, 1995b), Sindbis virus (Levine et al, 1993;Esolen et al, 1995), reovirus (Tyler et al, 1995), and influenza viruses (Takizawa et al, 1993;Fesq et al, 1994). Apoptosis is characterized by distinctive morphological and biochemical features.…”
Section: Introductionmentioning
confidence: 99%